iRoot SP Promotes Osteo/Odontogenesis of Bone Marrow Mesenchymal Stem Cells via Activation of NF-κB and MAPK Signaling Pathways - Xiao Wu; Ming Yan; Jiamin Lu; Xingyun Ge; Yuzhi Li; Minxia Bian; Lin Fu; Jinhua Yu (Stem Cells International)
The regeneration of bone and tooth tissues, and related cellular therapies, has attracted widespread attention. Bone marrow mesenchymal stem cells (BMSCs) are potential candidates for such regeneration. iRoot SP is a premixed bioceramic root canal sealer widely used in clinical settings. However, the effect of iRoot SP on the biological features of BMSCs has not been elucidated. In the present study, we found that 0.2 mg/ml iRoot SP conditioned medium promoted osteo/odontogenic differentiation and enhanced mineralization of BMSCs without affecting the proliferative ability. Mechanistically, the NF-κB and MAPK signaling pathways were activated in SP-treated BMSCs, and differentiation was inhibited when cultured with the specific inhibitor. Taken together, these findings demonstrate that iRoot SP promotes osteo/odontogenic differentiation of BMSCs via the NF-κB and MAPK signaling pathways, which could provide a new theoretical basis for clinical applications of iRoot SP and a new therapeutic target for the regeneration of bone and tooth tissue in the future.